2012
DOI: 10.1155/2012/247070
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of 1.55 μm Wavelength Single-Mode Vertical-Cavity Surface-Emitting Laser Output under External Optical Injection

Abstract: We review the temporal dynamics of the laser output spectrum and polarization state of 1.55 μm wavelength single-mode (SM) vertical-cavity surface-emitting lasers (VCSELs) induced by external optical beam injection. Injection of an external continuous-wave laser beam to a gain-switched SM VCSEL near the resonance wavelength corresponding to its main polarization-mode output was critical for improvement of its laser pulse generation characteristics, such as pulse timing-jitter reduction, linewidth narrowing, pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Because VCSELs play the important roles in many fields, study on the nonlinear dynamics of VCSELs is particularly important and has been widely studied. Previous theoretical and experimental research studies have demonstrated that VCSELs exhibit a wide range of nonlinear dynamics under external perturbations including optical injection, optical feedback or optoelectronic feedback (OEF) [6]- [27]. For OEF, the laser output is converted into electric current through a photodetector and fed back to the laser.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because VCSELs play the important roles in many fields, study on the nonlinear dynamics of VCSELs is particularly important and has been widely studied. Previous theoretical and experimental research studies have demonstrated that VCSELs exhibit a wide range of nonlinear dynamics under external perturbations including optical injection, optical feedback or optoelectronic feedback (OEF) [6]- [27]. For OEF, the laser output is converted into electric current through a photodetector and fed back to the laser.…”
Section: Introductionmentioning
confidence: 99%
“…Different phenomena of VCSELs subject to optical injection or optical feedback have been studied and reported in recent years. These phenomena include polarization switching (PS) and bistability [6]- [13]; injection locking [14], and [15]; nonlinear dynamics, such as regular pulsing (RP), quasiperiodic pulsing (QP), chaos [16]- [27], etc.…”
Section: Introductionmentioning
confidence: 99%